2012
DOI: 10.13057/biodiv/d130208
|View full text |Cite
|
Sign up to set email alerts
|

The wild plants used as traditional medicines by indigenous people of Manokwari, West Papua

Abstract: Lense O. 2012. The wild plants used as traditional medicines by indigenous people of Manokwari,. The aims of the research were to identify the main plant species which are used as traditional medicines by native people in Manokwari District, West Papua Province and also to describe the method of preparation and uses of some of the medicinal plants. This research was conducted in seven sub-districts, ie. Manokwari, Ransiki, Kebar, Wasior, Mimyambouw, Merdey and Anggi-Sururey subDistrict. Information recorded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
(18 reference statements)
0
9
0
3
Order By: Relevance
“…Zuhud (2009) has studied the potential of Indonesian tropical forests as a support for natural medicines for protecting national health. Lense (2012) has studied wild plants as traditional medicines in Manokwari, West Papua, Indonesia. Silalahi et al (2015) have reported the local knowledge of medicinal plants and diversity of medicinal plants in the Kabanjahe traditional market, North Sumatra, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Zuhud (2009) has studied the potential of Indonesian tropical forests as a support for natural medicines for protecting national health. Lense (2012) has studied wild plants as traditional medicines in Manokwari, West Papua, Indonesia. Silalahi et al (2015) have reported the local knowledge of medicinal plants and diversity of medicinal plants in the Kabanjahe traditional market, North Sumatra, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…C. fruticosa (L.) A. Chev. merupakan tumbuhan monokotil dengan dengan penebalan pada bagian batang dan rhizoma (Lense 2012;Fouedjou et al 2016;Reddy et al 2016).…”
Section: Cordyline Fruticosa (L) a Chevunclassified
“…Papua sebagai bahan pangan maupun sebagai bahan obat, diantaranya adalah untuk menyembuhkan luka, menurunkan demam dan meringankan nyeri (Lense, 2012 adanya tansisi electron dari gugus tidak jenuh (Mahatriny, Payani, Oka, & Astuti, 2014 (Maulita, Arvin , & Sumantri , 2009). Alkaloid mampu merusak lapisan peptidoglikan sehingga dinding sel bakteri lisis dan menyebabkan kematian sel bakteri (Darsana , Besung, & Mahatmi, 2012).…”
Section: Daun Gatal Tersebar Telah Banyak Dimanfaatkan Oleh Masyarakaunclassified